2014
DOI: 10.1111/1440-1681.12186
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of ebselen in traumatic brain injury model: involvement of nitric oxide and p38 mitogen‐activated protein kinase signalling pathway

Abstract: Previous investigations have found that ebselen is able to treat neurodegenerative diseases caused by radical and acute total cerebral ischaemia. The aim of the present study was to investigate the neuroprotective effects of ebselen in a traumatic brain injury (TBI) model. Ninety Sprague-Dawley rats were randomly divided into five groups (n = 18 in each): (i) sham operation; (ii) an injury model group; (iii) low-dose (3 mg/kg) ebselen-treated group; (iv) a moderate-dose (10 mg/kg) ebselen-treated group; and (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…Our results were consistent with a previous study [27]. Unlike our study, Wei et al demonstrated that both a 10 mg/kg and a 30 mg/kg dose of ebselen administered by an intragastric route significantly reduced the NO and iNOS mRNA levels in rats with a traumatic brain injury model in a dose-dependent manner [28]. In our study, a 30 mg/kg dose of ebselen did not reduce NO levels or the number of iNOS positive cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our results were consistent with a previous study [27]. Unlike our study, Wei et al demonstrated that both a 10 mg/kg and a 30 mg/kg dose of ebselen administered by an intragastric route significantly reduced the NO and iNOS mRNA levels in rats with a traumatic brain injury model in a dose-dependent manner [28]. In our study, a 30 mg/kg dose of ebselen did not reduce NO levels or the number of iNOS positive cells.…”
Section: Discussionsupporting
confidence: 93%
“…Activation of p38 leads to the production of cleaved caspase-3 and a reduction in bcl-2, thus resulting in apoptotic neuronal death ( Raghupathi et al, 2003 ). Previous studies have shown significant activation of p38 in the brain after TBI ( Tang et al, 2012 ; Wei et al, 2014 ; Li et al, 2017 ; Yang et al, 2017 ). Blocking p38 activation attenuates matrix metalloprotein-9 (MMP-9) expression and thus mitigates brain edema following TBI ( Tang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 86%
“…Following bilateral entorhinal cortex lesion, GPx4 expression is upregulated in reactive astrocytes of lesioned areas but not in neurons. The GPx mimic, Ebselen [2-phenyl-1,2-benzisoselenazol-3(2H)-one], is reported to reduce NO levels and modulate the TL4-mediated p38-MAPK pathway after weight drop injury in rats (Wei et al, 2014). …”
Section: Therapeutic Strategies Targeting Lipid Peroxidationmentioning
confidence: 99%